Pedagogía de los derechos humanos en la educación para el trabajo y el desarrollo humano (2021)
The present study is developed in the context of training for work and human development, in the pedagogical construction of rights through the area of attitudinal value development with the aim of proposing the development of pedagogical strategies with a Human Rights approach that supports comprehensive professional training, based on the qualitative-descriptive approach, which is adjusted to a comprehensive interpretive look from the analysis methodology of textual and discursive content- The textual content is structured from three categories with their subcategories: Human Rights Approach, content with a rights focus and pedagogical actions with a Rights Approach, with the analysis of the results through the Atlas Ti Software. It is established that the Pedagogical Model Institutional of Integral Professional Training of the SENA and the Institutional Educational Project, in theory, contains the methodological guidelines for the education in Human Rights; and the perception of the instructors is to recognize a lack of knowledge in the content and the way of application with the need to structure the area of attitudinal value development as the tool for the development of competences and capacities that can guide the formation of economic, social and cultural rights.